Renal Lobulation-A Benign Macroanatomical Variation? - Serghei Covantsev; Oleg Arnaut; Karina Mulaeva; Olga Belic (MDPI AG, 2023)
Introduction: Renal lobulation (also known as fetal or embryonic lobulation) is a rare variation during development in which renal lobules have a visible anatomical space between them, and this can be seen in 0.5-4% of adults. Material and methods: this study was conducted on 54 human kidneys from patients who died due to causes unrelated to renal pathology which were fixed in a 10% formaldehyde solution and then carefully dissected. Results: The group with fetal lobulation (n = 16) was associated with a length M = 9.89 (SD = 0.6, p = 0.15). By comparison, the kidneys without lobulation (n = 38) were associated with a numerically longer length M = 10.29 (SD = 0.607, p = 0.098). To test the hypothesis that lobulation is associated with a statistically significant different length a Mann-Whitney test was performed, which indicated that the length of the kidneys is smaller in scase of lobulation U = 198, Z = −2.04, p = 0.04. Cross-tabulation also demonstrated that kidney lobulation may be influenced by the presence of polar arteries with r = 0.41 (p < 0.02). The likelihood ratio was 7.28, df 1, p = 0.003, with an odds ratio of 6.857 (CI 95% = 1.84-25.61). Logistic regression analysis demonstrated that kidneys with lobulation were 6.85 times more likely to have polar arteries than kidneys without lobulation. Conclusions: the data from our research indicate that even though no pathological conditions have been linked with lobulated kidneys, the incidence of vascular variations (specifically polar arteries) is higher when there is persistent fetal lobulation.